Cluster clinic model reduces travel distance to access care and improves access equality - K. Johnstone; S. Turner (Public Health in Practice)
Background: Travel distance is a barrier to accessing care, especially in large, sparsely populated areas. The cluster clinic model aims to provide paediatric scheduled care in the community setting within NHS Grampian. This work aims to quantify the impact of this model on travel distance and equality of access. Study design: Observational analytical study comparing three models of service delivery. Methods: Three models were compared: All clinics delivered at Royal Aberdeen Children's Hospital (model A), all clinics delivered at cluster clinics (model B), and clinics at both hospital and cluster clinics (model C). Shortest drivable distance from home to clinic was calculated for all children in Aberdeen City and Aberdeenshire. Equality of access was assessed using a Gini coefficient, with values closer to 0 representing better equality, and 1 representing worse equality. Results: In model A, median travel distance was 8.64miles (Q1: 2.96miles, Q3: 25.7miles, Gini: 0.491). For model B, median travel distance was 3.14miles (Q1: 1.46miles, Q3: 9.07miles, Gini: 0.480). In model C, median travel distance was 3.13miles (Q1: 1.35miles, Q3: 9.07miles, Gini: 0.490). No association with index of multiple deprivation was found in any model. Conclusions: The cluster clinic model both significantly reduces travel distance, whilst simultaneously improving access equality. This methodology should be considered to prospectively evaluate implementation of similar models elsewhere.